FcRL4 Expression Identifies a Pro-inflammatory B Cell Subset in Viremic HIV-Infected Subjects - Siewe, Basile; Nipper, Allison J.; Sohn, Haewon; Stapleton, Jack T.; Landay, Alan (Frontiers in Immunology, 2017)
In autoimmune diseases, Toll-like receptor (TLR)-stimulated pro-inflammatory IL-6 secreting B cells exert pathogenic roles. Similarly, B cell Fc receptor-like 4 (FcRL4) expression amplifies TLR stimulation, and in rheumatoid arthritis patients FcRL4 expression identifies a pro-inflammatory B cell subset. B cells from HIV-infected subjects also express heightened levels of FcRL4 and secrete high levels of IL-6: a critical mediator of HIV disease progression. In this study we sought to determine if FcRL4 identifies a pro-inflammatory B cell subset in HIV-infected subjects and further, elucidate the mechanisms underlying FcRL4 amplification of TLR stimulation. We determine that tissue-like memory B cells express the highest endogenous levels of FcRL4 positively correlating with IL-6 expression (p=0.0022, r=0.8667), but activated memory B cells exhibit the highest frequency of FcRL4hiIL-6hi cells. FcRL4hi B cells exhibit an activated TLR-signaling pathway identified by elevated phosphorylation levels of: pERK (p=0.0373), p38 (p=0.0337), p65 (p=0.1097) and cJUN (p=0.0239), concomitant with significantly elevated expression of the TLR-signaling modulator Hematopoietic cell kinase (HcK, p=0.0414). Compared to FcRL4neg B cells from healthy controls, TLR9-stimulated FcRL4pos B cells express significantly higher levels of lL-6 (p=0.0179). Further, TLR9-stimulated B cells also upregulate the expression of FcRL4 (p=0.0415) and HcK (p=0.0386). In B-cell lines, siRNA-mediated HcK knockdown down-modulates TLR9-induced FcRL4-mediated activation quantified by CD23 upregulation (p=0.0553). We present data suggesting that in viremic HIV infected individuals, FcRL4 expression identifies unique IL-6 producing pro-inflammatory B-cell subsets. Further, TLR-stimulation likely modulates FcRL4 expression and FcRL4 expression is associated with Hck, potentially enhancing the activation of TLR-signaling associated transcription factors. Pathogenic B-cells have been identified in other disease settings and this study represents a novel report describing a pro-inflammatory B cell subset in HIV infected patients.